The Effect of Interactive WordWall Media on Early Reading Ability Slow Learner Students - Sunarni; Bayu Pamungkas (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the effect of using interactive WordWall media on the early reading ability of Grade II slow learner students in elementary school. Employing a quasi-experimental design with pretest-posttest control group, 40 slow learner students were divided equally into experiment and control groups. The experimental group received instruction using WordWall interactive activities, while the control group received conventional reading instruction. Data were collected via standardized reading fluency and comprehension tests, observation checklists, and student interviews. Results showed that the experimental group exhibited significantly greater improvements in reading ability (fluency, word recognition, and comprehension) compared to the control group (p < 0.05). The effect size (Cohen’s d) was medium to large, indicating a practically meaningful impact. Compared with prior studies in Indonesia and abroad that used WordWall or other gamified media, our findings confirm and extend evidence that interactive media can support reading development especially for weaker learners. This research contributes novelty by focusing specifically on slow learner students in lower primary reading and demonstrates that WordWall—previously used predominantly for vocabulary or language learning—can be adapted for reading remediation. Implications for educational practice and future longitudinal studies are discussed.